MONEY IN ISLAM: A SOCIAL CONTRACT PERSPECTIVE - Alam Asadov (Jurnal Internasional Ekonomi Islam, 2020)
Money being the blood of economy and main determinant of many human transactions is an important topic to be discussed. Throughout the history there have been many who tried to explain nature and desired form of money in their writings. This topic has not skipped writings of Islamic religious scholars and economists as well. Current work attempts to review some of recent literature about essence of money from Islamic prospective. The review works which express different views from both Religious and Economic perspectives by six selective authors with diverse backgrounds. In the review, we mainly focus at the role of money as a social contract (between State and its citizens) and at some Shari’ah compliance issues faced by commodity (gold and silver) and paper (fiat) currencies. Some of our important findings show that the commodity currency had problem of breach from State’s side in some occasions, while paper currency is considered as an invalid contract by majority of the authors. The work concludes with summary of the authors’ opinions and points out their relative strengths and weaknesses from Shari’ah and Economic prospective, which is extended with some recommendations for further research.